Kindergarten's Gross Motor Learning Model Based on Playing Activities as a Basis for Character Building - Gusril,; Hauw Sin, Tjung; Komaini, Anton; Sazeli Rifki , Muhamad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was kindergarten’s gross motor learning model based on playing activities as a basis for character building. The quantitative research was done using a quasi-experiment. The population of the research, 78 students, consists of Class A (38 students) and Class B (40 students). The research sample was taken by using random sampling and getting 38 students from Class A from Mutiara Ananda Kindergarten in Koto Tangah District. The data collection instruments were observation, interview, questionnaire, and gross motor test. Data analysis techniques are using quantitative analysis that is percentage and t-test. The results of the study conclude: The kindergarten’s gross motor learning model based on playing activities as a basis for character building is effective.